Makna Pesan Pada Gerakan Tarian Sada Dan Sabai Dalam Tradisi Budaya Komering Di Kabupaten Ogan Komering Ulu Timur - Nurlia Nurlia; Akhmad Rosihan; Bianca Virgiana (Universitas Baturaja, 2020)
Communication is also very closely related to a culture, because by communicating humans get an idea and ideas that ultimately shape the work of art, and the work of art is done by the ancestors and then carried out continuously into his generation, with the process of creating a culture. one of the cultures that use communication is the Sada Dance and the Sabai Cultural tradition of East Ogan Komering Ulu Regency, this dance is a dance for the East Ogan Komering Ulu Komering wedding celebration which has a meaning of communication.This research uses the Symbolic Interaction Theory is a movement in sociology, focusing on the ways humans make meaning and order in society through thought and action. In this study, researchers used constructivist paradigms with qualitative research types and descriptive qualitative methods. The results of this study indicate that the Sada and Sabai dance is a traditional dance typical of East Ogan Komering Ulu Regency, this dance has meaning on the movement and has meaning on the symbols that exist in this dance. The meaning of the sada and sabai dance is happiness, for the symbols of this welcoming dance by using the tigol, shawl, fan dance and kulintang music accompaniment that are characteristic of the people of East Ogan Komering Ulu. And it is associated with the Symbolic Interaction theory that the meaning of Sada and Sabai is created through a communication process and modified in a particular symbol that is meaningful to produce mutual agreement and is culturally known and accepted by the public.